Women Through Anti-Proverbs - Litovkina, Anna T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book examines stereotypical traits of women as they are reflected in Anglo-American anti-proverbs, also known as proverb transformations, deliberate proverb innovations, alterations, parodies, variations, wisecracks, fractured proverbs, and proverb mutations. Through these sayings and witticisms the author delineates the image of women that these anti-proverbs reflect, her qualities, attributes and behavior. The book begins with an analysis of how women's role in the family, their sexuality and traditional occupations are presented in proverbs, and presents an overview of the genre of the anti-proverb. The author then analyses how this image of women is transformed in anti-proverbs, sometimes subverting, but often reinforcing the sexist bias of the original. This engaging work will appeal to students and scholars of humour studies, paremiology, gender studies, cultural studies, folklore and sociolinguistics alike.
Part I 1 1 Women in American Proverbs.-2 Anti-Proverbs -- Part II -- 3 A Woman's Nature as Represented in Anglo-American Anti-Proverbs -- 4 "Give a Girl Enough Rope and She'll Ring the Wedding Bell": The Nature of Young Women, Girls, Daughters and Brides as Represented in Anglo-American Anti-Proverbs -- 5 "Spinsters Live Longer Than Married Women Because Where There's Hope There's Life": Spinsters as Represented in Anglo-American Anti-Proverbs -- 6 "Behind Every Man Who Lives Within His Income Is a Wife Who Doesn't": The Figure of Wife as Portrayed in Anglo-American Anti-Proverbs -- 7 "Many a Widow Finds It Easy to Marry Again Because Dead Men Tell No Tales": Widows as Revealed Through Anglo-American Anti-Proverbs -- 8 "On the Matrimonial Sea, the Hand That Rocks the Cradle Very Seldom Rocks the Boat": Mothers as Revealed Through Anglo-American Anti-Proverbs -- 9 "When the Mother-In-Law Comes in at the Door, Love Flies Out of the Window": The Mother-in-Law as Reflected in Anglo-American Anti-Proverbs -- 10 "You Know a Bad Beginning Makes a Good Endin',".as the Old Woman Said: Generic Old Women as Represented in Anglo-American Anti-Proverbs -- 11 "The Breasts on the Other Side of the Fence Look Greener": Women's Sexuality as Revealed Through Anglo-American Anti-Proverbs -- 12 "Never Send a Boy to Do a Man's Job-Send a Woman": Female Professions and Occupations -- Contents -- Conclusion -- References -- Index .
Keywords: Sociolinguistics; Sex; Feminism; Feminist theory; Ethnology -- America; Culture; Sociolinguistics; Gender Studies; Feminism and Feminist Theory; American Culture